Seawater intrusion regulates microbial community structure and functional potential in subterranean estuaries of the Yangtze River - Zhao, Yunduo; Li, Dongsheng (Frontiers in Microbiology, 2025)
Subterranean estuaries (STE) regulate coastal biogeochemistry through microbial activity. However, responses of microbial community structure and function to seawater intrusion in STE under climate change remain unclear. This study employed isotopic techniques and high-throughput sequencing to analyze the changes in microbial community under seawater intrusion. The results showed that the microbial diversity showed positive correlations with the proportion of seawater (PSW), whereas the abundances of predicted functional genes for nitrogen, phosphorus and sulfur cycling exhibited negative correlations with the PSW. Compared to the layer A (relatively high degree of seawater intrusion), layers B and C (relatively low degree of seawater intrusion) showed declines of 80.4% and 78.1% in Chao index and 19.2% and 15.2% in Shannon index, respectively. Predictive functional profiling further suggested a significant decrease in genes for labile carbon decomposition and a significant increase in genes for recalcitrant carbon decomposition, nitrogen, phosphorus and sulfur cycling in layers B and C. The microbial co-occurrence networks in layer A exhibited more node and high stability, whereas those in layer C were high modularity. Different from the traditional view that salinity is the main environmental filter, we found that the selective pressure of specific ions (such as NH₄+, PO₄2−, SO₄2−) could better explain the variations of the microbial community than the total salinity index in the STE. This revealed the response mechanisms of coastal microbial communities to seawater intrusion and provide a theoretical basis for predicting coastal biogeochemical cycling.